Water resource economy: the challenge of efficiently allocating a(n increasingly) sparse resource - Lanna, Antonio Eduardo (Estudos Avançados, 2008)
This paper presents and analyzes water resource prospective scenarios from which the National Water Resources Plan has established its strategies, goals and programs. Based on these data the future tendencies for 4 water user sectors with greatest dynamic and conflict potential are analyzed: irrigated agriculture, energy generation, navigation and basic sanitation. Issues which cannot be ignored are the climate changes and how they can affect water supply and demands. From these analyses some conclusions and recommendations are proposed, aiming the anticipation of the future and to prepare public, private and third sector actors to promote rational use of water, focusing on the sustained development. Or, as economist used to say: the optimal allocation of a scarce resource.